Sistem Kendali Upper Cylinder Berbasis Programmable Logic Control pada Area Section Mill di PT. Krakatau Baja Kontruksi - Galih Aji Pramono; Endi Permata (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The smooth production process is one of the factors supporting the success of a manufacturing industry in producing quality products, timely completion of manufacture and low production costs. Industrial machines are an important factor in a manufacturing industry besides reliable human resources (HR) and other supporting facilities, so that industrial machines require special attention that is carried out on an ongoing basis in order to support the smooth operation of an industry. Practical work at PT. Krakatau Steel Construction is carried out in the Maintenance division, especially the electrical parts. In practice, the authors conducted field research by participating directly in the process of caring for and maintaining each machine instrument used by the company, especially field research that discussed the upper cylinder control system based on programmable logic control in the section mill area at PT. Krakatau Steel Construction. . In this study using field research techniques where the author conducted field research by participating directly in the process of caring for and maintaining each machine instrument used by the company accompanied by industrial supervisors and maintenance division employees for 1 month.